The Goose that laid the Golden Eggs - Mackinnon, Mairi; Flutter, Louise; Howarth, Daniel; Kelly, Alison; Punter, Russell; Sims, Lesley (London Usborne, 2006)
Tom and Elena are poor but happy until the day Tom finds that their little white goose has laid a golden egg. Every morning they find another egg, every day they grow richer- but what happens when one golden egg a day just isn't enough?
English Stories
based on the fable by Aesop
Keywords: English stories